Corporate governance of sustainability a co-evolutionary view on resource management - Bleischwitz, Raimund; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
This book considers corporate governance of sustainability from a co-evolutionary perspective. It explores the linkages between pro-active approaches at the corporate level, market-based incentives and environmental networks involving various actors. Relevant theory on corporate governance, competition, market failures and regulatory tools is also examined. The authors go on to present an assessment methodology suitable for empirical network analysis at the meso-level, and demonstrate its application using eight case studies. Based on the findings of this research Raimund Bleischwitz and his team draw important conclusions for policy analysis and sustainability assessments and the actors involved.
pt. 1. Analysing corporate governance of sustainability : insights from research and policy analysis -- pt. 2. Network analysis and evaluation -- pt. 3. Case-studies on sustainability at the meso-level -- pt. 4. Conclusions.
Includes bibliographical references (p. 246-267) and index.
Keywords: Corporate governance; Corporate governance -- Case studies; Sustainable development; Sustainable development -- Case studies; Electronic books